Incidental finding of a giant intracardiac angioma infiltrating both ventricles in a 35-year-old woman: a case report. (December 2016) - Hirschberg, K.; Wiedmann, F.; Zitron, E.; Fortner, P.; Riffel, J.; Chorianopoulos, E.; Gdynia, G.; Mechtersheimer, G.; Andrassy, M.; Szabó, G.; Arif, R.; Katus, H.; et al.
Abstract Background Primary cardiac tumors are rare and often asymptomatic or present with unspecific symptoms. Benign cardiac tumors of vascular origin are especially rare, with only few existing data in the literature. Case presentation A 35-year-old Caucasian female patient presented to our department with an asymptomatic giant intracardiac angioma infiltrating both ventricles. Evaluation of this tumor involved electrocardiography, echocardiography, cardiac magnetic resonance imaging, coronary angiography, an open myocardial biopsy, and histological examination of the resected specimen. Because our patient was asymptomatic, she was managed conservatively with regular follow-up. We discuss the treatment options available in comparison with similar cases. Conclusion Diagnosis and therapy of benign cardiac tumors, especially of asymptomatic lesions, can be a challenge. There is no evidence available to help in the management of such patients. An extensive evaluation is needed with different imaging modalities, and case-specific decisions should be made that involve experts in cardiology, cardio-oncology, and heart surgery.